1998
DOI: 10.1021/ac9707085
|View full text |Cite
|
Sign up to set email alerts
|

Head-Column Field-Amplified Sample Stacking in Binary System Capillary Electrophoresis. 2. Optimization with a Preinjection Plug and Application to Micellar Electrokinetic Chromatography

Abstract: In capillary electrophoresis, head-column field-amplified sample stacking (FASS) provides the largest sensitivity enhancement of all electrokinetic concentration techniques (Zhang, C.-X.; Thormann, W. Anal. Chem. 1996, 68, 2523). Application of head-column FASS to the analysis of closely related opioids by capillary zone electrophoresis in binary systems with ethylene glycol is described. It is shown that sample condensation is further increased about 2-fold by introduction of a preinjection plug, i.e., introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(85 citation statements)
references
References 52 publications
(232 reference statements)
1
83
0
1
Order By: Relevance
“…The former is obtained thanks to different strategies mainly based on on-line sample preconcentration, obtained easily in CE by electrokinetic (EK) injection [2]. Such injection can lead to over 1000-fold sensitivity enhancement compared to conventional hydrodynamic (HD) injection [3]. The second can be achieved with the on-line coupling of CE with MS through an ESI source, which is a powerful hyphenated technique [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The former is obtained thanks to different strategies mainly based on on-line sample preconcentration, obtained easily in CE by electrokinetic (EK) injection [2]. Such injection can lead to over 1000-fold sensitivity enhancement compared to conventional hydrodynamic (HD) injection [3]. The second can be achieved with the on-line coupling of CE with MS through an ESI source, which is a powerful hyphenated technique [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…As analytes reach the sample matrix/BGE interface, their velocities decrease, resulting in a stacking of the analytes into narrow bands [183]. In CZE applications utilizing FASS, studies have reported on a doubling of sample stacking efficiencies [185] and 1000-fold increases in sensitivity [186], resulting in considerable improvements in loadability over conventional CZE.…”
Section: Preconcentration Techniques For Intact Proteins In Capillarymentioning
confidence: 99%
“…The size of the preinjection plug also has an effect on the peak shape and hence on the detection limits and the resolution [43][44][45]. Electropherograms obtained when varying the time for the hydrodynamic injection of the solvent plug between 120 and 240 s are shown in Fig.…”
Section: Fassmentioning
confidence: 99%